The contribution of the Education Program for Health work in “being a SUS professional” - Cardoso Lisboa Pereira, Simone; Rodrigues Macedo, Thamiris; dos Santos, Luana Caroline; Lindgren Alves, Claudia Regina (O Mundo da Saúde, 2018)
The proposal of the Educational Program for Health Work (EPW - Health) provides opportunities for higher education institutions to train health professionals with a profile appropriate for social needs, based on skills and ability to work in teams, giving full attention to health, to interdisciplinarity and to humanistic aspects, besides favoring the implementation of health services that are more resolvable and adequate to the needs of the population. Against this background, the aim was to delineate social representations of “Being a SUS Professional” from the perspective of Health Sciences undergraduates. Secondary data were obtained from 234 candidates who entered the EPW-Health, the third time it was offered in the institution, from a free recall projective test through the inducing term "Being a SUS professional", applied by mentors of the Program. The EVOC® software was used for analysis, and the products were organized according to previous experience in the program. Between those people with previous experience (n=98) representational components aligned in the SUS, such as “Multi-professional service”, “Universality”, “Integrality” and “Humanization” were found. From the perspective of another group there was no direct allusion to the guidelines and principles of the SUS as the core elements of social representations. These results indicate that the experience in EPW-Health can contribute greatly for training of health professionals aware of the social demands of SUS.